Co-Producing Mobilities: negotiating geographical knowledge in a conference session on the move. Issue 3 (2nd July 2016) - Cook, Simon; Davidson, Anna; Stratford, Elaine; Middleton, Jennie; Plyushteva, Anna; Fitt, Helen; Cranston, Sophie; Simpson, Paul; Delaney, Hannah; Evans, Kate; Jones, Amy; Kershaw, Jonathan; et al.
Abstract: In an experimental session entitled Co - Producing Mobilities held at the 2014 Royal Geographical Society-Institute of British Geographers Annual Conference, 20 mobility scholars travelled around London on foot, by bus and by Tube to investigate how mobilities could be considered co-produced. In this paper, 18 participants reflect on this collaborative experiment and on how it influenced their thinking about mobilities, geographical knowledge and pedagogy. Contributions cast light on the function of conferences and the multiple forms of pedagogy they enable, and provide guiding resources for those now wanting to continue such experiments.